2020
DOI: 10.1155/2020/8840245
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Presentation of Extrapulmonary Sarcoidosis

Abstract: Sarcoidosis is an idiopathic, chronic, multisystem, granulomatous, inflammatory disease involving almost all organs. Sarcoidosis can occur with an atypical presentation of hepatosplenic involvement, like in the case of our patient. In this case report, we present a rare case of extrapulmonary sarcoidosis with isolated involvement of the liver and spleen in a 39-year-old Caucasian female. There is a possibility of this isolated involvement of an organ in the complete absence of pulmonary disease, which makes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The indication for therapy has been based on the presence of symptoms and biochemical liver derangement, with or without evidence of fibrosis/ cirrhosis on imaging. 9 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 The dosage of corticosteroids, particularly prednisolone, varies from 20 mg to 60 mg per day. 12 , 27 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 In our review, some of the studies used dosages of 0.5 mg to 1 mg/kg/day, 45 , 46 , 47 and none of the studies reported a prednisolone dose of greater than 1 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indication for therapy has been based on the presence of symptoms and biochemical liver derangement, with or without evidence of fibrosis/ cirrhosis on imaging. 9 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 The dosage of corticosteroids, particularly prednisolone, varies from 20 mg to 60 mg per day. 12 , 27 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 In our review, some of the studies used dosages of 0.5 mg to 1 mg/kg/day, 45 , 46 , 47 and none of the studies reported a prednisolone dose of greater than 1 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this low quality evidence data, it can be summarized that corticosteroids are the main first‐line treatment in hepatic sarcoidosis. The indication for therapy has been based on the presence of symptoms and biochemical liver derangement, with or without evidence of fibrosis/ cirrhosis on imaging 9,27–36 . The dosage of corticosteroids, particularly prednisolone, varies from 20 mg to 60 mg per day 12,27,37–44 .…”
Section: Discussionmentioning
confidence: 99%
“…Granulomatous mastitis treatment is widely variable depending on multiple factors and includes corticosteroids, surgery, methotrexate, and other immunosuppressive regimens. 16 A high success rate of remission has been demonstrated with the use of high-dose steroids. However, the undesirable side effects have limited its use.…”
Section: Discussionmentioning
confidence: 99%
“…However, the undesirable side effects have limited its use. 16 Conversely, studies have reported plausible outcomes and a lower recurrence rate of GM with the use of methotrexate as a single-drug regimen or in addition to low-dose corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic involvement of systemic sarcoidosis is relatively common, and although it is usually asymptomatic, it can rarely lead to complications including cirrhosis and portal hypertension 1–5 . Isolated hepatic involvement of sarcoidosis is very rare 6–8 …”
mentioning
confidence: 99%